IL-1 family cytokines trigger sterile inflammatory disease - Lukens, John R.; Gross, Jordan M.; Kanneganti, Thirumala-Devi (Frontiers in Immunology, 2012)
Inflammation plays vital roles in protective responses against pathogens and tissue repair, however improper resolution of inflammatory networks is centrally involved in the pathogenesis of many acute and chronic diseases. Extensive advances have been made in recent years to define the inflammatory processes that are required for pathogen clearance, however in comparison, less is known about the regulation of inflammation in sterile settings. Over the past decade non-communicable chronic diseases that are potentiated by sterile inflammation have replaced infectious diseases as the major threat to global human health. Thus, improved understanding of the sterile inflammatory process has emerged as one of the most important areas of biomedical investigation during our time. In this review we highlight the central role that interleukin-1 (IL-1) family cytokines play in sterile inflammatory diseases.